Mid-Infrared ZnS Ridge Waveguide Fabricated by Femtosecond Laser Ablation Combined With Ion Irradiation - Zhang, Xinbin; Cheng, Yazhou; Zhang, Yongcheng (Frontiers in Physics, 2021)
We have experimentally studied the fabrication of ridge waveguides in zinc sulfide (ZnS) crystal by femtosecond laser ablation combined with Kr8+ ion irradiation. At the wavelength of 4 μm, the waveguide at TE mode shows better guiding properties than TM mode. The transmission performance of the waveguide is improved by using thermal annealing technology to reduce the color centers and point defects in the waveguide. The waveguide propagation loss at TE mode at 4 μm wavelength is reduced to as low as 0.6 dB/cm after annealing. Raman spectroscopy shows that Kr8+ ion irradiation does not cause large lattice damage to ZnS crystal.